MIGRATION OF THE LANDSCAPE ZONES OF THE RA IN THE CONTEXT OF GLOBAL CLIMATE CHANGES (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
In the work was calculated the coefficient of discomfort (its average annual value) of landscape zones widespread in the RA. Through its analysis, migration and transformation of landscape zones were identified, an analysis and assessment of the consequences were made.
Keywords: discomfort rate; landscape migration; landscape transformation; reference landscapes; degradation; desertification; biocenosis; biodiversity